Molecular recognition of biomolecules by chiral CdSe quantum dots - GOUNKO, IOURI; PURCELL-MILTON, FINN (My University, 2016)
Molecular recognition is one of the most important phenomena in Chemistry and Biology. Here we present a new way of enantiomeric molecular recognition using intrinsically chiral semiconductor nanocrystals as assays. Real-time confocal microscopy studies supported by circular dichroism spectroscopy data and theoretical modelling indicate an ability of left-handed molecules of cysteine and, to a smaller extent, histidine and arginine to discriminate between surfaces of left- and right-handed nanocrystals.
PUBLISHED
Cited By :3 Export Date: 28 February 2017
Keywords: nanocrystals; nanocrystals